Efforts To Improve Clean Water Quality To Support Community Health - Anatolia S.M. Exposto, Levi; Nahak Lino, Martinus; A.C. Quim, Jimedio; Juvi Goncalves, Marilia; Pereira Vicente, Honorio (Rifa'Institute, 2021)
Water is a fundamental part for every human being to survive and maintain his health, and therefore must also be seen as a major element in the fulfillment of the right to a decent standard of living. Water is the source of life for living things, especially humans, which develop with various kinds of basic human needs. Water is a primary need that is needed for daily needs such as drinking, cooking, bathing to industrial processing needs so that the function of water is not only limited to carrying out economic functions, but also as a social and cultural function. The water sector is getting significant attention. Therefore, the goal of Sustainable Development Goals 6thensures the availability and sustainable management of clean water and sanitation for all. In order to achieve the goal of clean water and proper sanitation by 2030. This article uses a Systematic review based on Preferred Reporting Items for Systematic Review & Meta-Analysis (PRISMA) in order to identify all published literature (2011-2021) using relevant keywords. The literature collected is sourced from databases from Google, Google Scholar, PubMed, Emerald Insight, DOAJ. A total of 70 pieces of literature were collected, after screening based on inclusion and exclusion criteria, there were 7 articles that would be analyzed further. After the literature is collected and analyzed, it can be found that clean water is one of the main elements in human life which is an integral part of all humans. Living things cannot live if there is no water, so water is needed to maintain the survival of living things. Water in the human body is very useful for filling fluids in the body by drinking water. In addition to thirst quencher and other main benefits of water for the body, water also has other benefits that are needed to support life. To get clean water, it must meet the requirements of 3 main parameters, namely the requirements, physical, chemical requirements, and bacteriological requirements. Clean water is very important for human life, but water quality must be maintained so that water does not endanger public health. By using clean water we can avoid diseases such as diarrhea, cholera, dysentery, typhoid, intestinal worms, skin diseases to poisoning. Clean water must meet 3 main parameters, namely; physical requirements, chemical requirements, and bacteriological requirements